2021
DOI: 10.1021/acs.jpcb.1c03674
|View full text |Cite
|
Sign up to set email alerts
|

Flying DNA Cation Radicals in the Gas Phase: Generation and Action Spectroscopy of Canonical and Noncanonical Nucleobase Forms

Abstract: Gas-phase chemistry of cation radicals related to ionized nucleic acids has enjoyed significant recent progress thanks to the development of new methods for cation radical generation, ion spectroscopy, and reactivity studies. Oxidative methods based on intramolecular electron transfer in transition-metal complexes have been used to generate nucleobase and nucleoside cation radicals. Reductive methods relying on intermolecular electron transfer in gas-phase ion–ion reactions have been utilized to generate a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…This was reversed in dGC4 + · where the cytosine π-orbital (MO 145α) was 0.05 eV higher than the guanine π-orbital (MO144α) (Figure S4, Supporting Information). We note that spin-unrestricted M06-2X calculations have been found to provide accurate excitation energies for cation radicals of several canonical and noncanonical nucleobases, ,,,, nucleosides, , and nucleotides, as determined by comparison with both experimental UV–vis action spectra and benchmarking on equation-of-motion coupled cluster calculations.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…This was reversed in dGC4 + · where the cytosine π-orbital (MO 145α) was 0.05 eV higher than the guanine π-orbital (MO144α) (Figure S4, Supporting Information). We note that spin-unrestricted M06-2X calculations have been found to provide accurate excitation energies for cation radicals of several canonical and noncanonical nucleobases, ,,,, nucleosides, , and nucleotides, as determined by comparison with both experimental UV–vis action spectra and benchmarking on equation-of-motion coupled cluster calculations.…”
Section: Resultsmentioning
confidence: 94%
“…Ionization of sugar-based C1′-C5′ nucleoside radicals has been addressed by DFT calculations . In addition, recent experimental and computational studies addressed the dynamics of electronic excitation in nucleobase and nucleotide cation radicals at high levels of theory. Recently, isomeric forms of nucleobase cation radicals have been discovered as stable gas-phase species and characterized by UV–visible photodissociation action spectroscopy . The noncanonical isomer of the thymine cation radical, [4-hydroxy-5-methylene-( 1,3H )­pyrimid-2-one] + · , was formed as a major component, along with the canonical isomer, by electron transfer oxidation of thymine in a copper-terpyridine complex .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, therefore, this Feature Article is not an extensive review of all PD spectroscopy strategies. For extended resources the reader is directed to the following reviews on ion-mobility, 4,39–41 the history of ion spectroscopy, 11,13,42 advances and developments in ion spectroscopy, 43 UV-vis photodissociation action spectroscopy, 44 lasers and mass spectrometry for structure determination, 45 conformer resolved photoinduced dynamics for neutral and ionic peptides, 46 action spectroscopy of DNA radical cations, 47 gas-phase dynamics including isomer selective spectroscopy, 48 biological relevant ions with room temperature 49–51 and cryogenic ion spectroscopy. 52,53…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive research of DNA ionization, structure characterization of highly reactive cation-radical intermediates remains challenging . Recent studies have indicated that DNA-related cation radicals, such as nucleobases, nucleosides, and oligonucleotides, can be generated in the gas phase, isolated by mass, and studied by tandem mass spectrometry in combination with action spectroscopy in the infrared or UV–visible regions . This technique relies on wavelength-dependent photodissociation whereby the photofragment ion production is used to reconstruct the absorption profile of the isolated ion .…”
Section: Introductionmentioning
confidence: 99%